2018
DOI: 10.1093/eurpub/cky038
|View full text |Cite|
|
Sign up to set email alerts
|

Morbidity and housing status 10 years after shelter use—follow-up of homeless men in Helsinki, Finland

Abstract: Homeless staying in shelters have high mortality and morbidity and most of those surviving, are in need of support in their everyday lives even years after the shelter period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Our results support the findings of several authors that homelessness is not only an independent risk factor of mortality, but also a persistent one over time. Stenius-Ayoade followed a large cohort of homeless people after shelter use in Helsinki (mean age: 49.4 years), and showed that 10 years after 52% were deceased, versus 14.6% of the age-matched control group, even if “only” 5% were still homeless [ 30 ]. For survivors, Oppenheimer showed that a history of homelessness (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support the findings of several authors that homelessness is not only an independent risk factor of mortality, but also a persistent one over time. Stenius-Ayoade followed a large cohort of homeless people after shelter use in Helsinki (mean age: 49.4 years), and showed that 10 years after 52% were deceased, versus 14.6% of the age-matched control group, even if “only” 5% were still homeless [ 30 ]. For survivors, Oppenheimer showed that a history of homelessness (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Substance use may act both as a cause and consequence of homelessness, 7 , 11 , 12 , 22 and each may compound the other 6 , 10 , 12 , 13 , 22 . Past research has found, for example, that substance use is associated with higher entry rates into and longer durations of homelessness 11 , 23 27 . Our understanding of the relationships between homelessness and substance use has been hindered by limitations in past research, including cross-sectional design or crude measures of homelessness and substance use.…”
Section: Introductionmentioning
confidence: 99%